Coupling and Decoupling Relationships between Energy Consumption and Air Pollution from the Transport Sector and the Economic Activity - Botzoris, George Nikiforos; Galanis, Athanasios T.; Profillidis, Vassilios A.; Eliou, Nikolaos E. (International Journal of Energy Economics and Policy, 2015)
In the present paper an analysis of whether and under which conditions coupling or decoupling exists between growth rates (as reflecting in GDP rates) of the economy and energy consumption and air pollution from the transport sector. An extensive time period from 1995 to 2012 is surveyed and divided into two periods, from 1995 to 2008 (growth period) and from 2008 to 2012 (recession period). The analysis is conducted for the 28 European Union countries and illustrates, for most of these countries, a coupling phenomenon for the growth period and a decoupling phenomenon for the recession period. This finding may be essential for the further institutional steps to be undertaken, in view of the reduction of CO2 and of energy conservation. Keywords: Coupling; Decoupling; Transportation; Environment; Sustainability JEL Classifications: H23; O44; R4; Q53